Penguatan Edukasi Persiapan Persalinan “Road To Gentle Birth” Bagi Ibu Hamil di Desa Jati, Jaten, Karanganyar - Aris Noviani; Siskana Dewi Rosita (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Gentle birth is a concept in childbirth that is carried out quietly. The purpose of this community service activity is to provide knowledge to pregnant women about childbirth preparation, signs of childbirth, labor pain management so that the delivery process runs smoothly and with minimal trauma for pregnant women in Jati-Jaten Village, Karanganyar. The methods used are presentations, video screenings, questions and answers, and practicums. Th epre-test and post-test were packed out in the cast of 15 statements, then actors were questioned to reply whether each statement was right or false. Statements on thepre-test andpost-test are acclimated to the material staged. As a resultant of this exertion, there was an addition in actors' science about mild birth, videlicet from a aggregate of 30 actors, in thepre-test responses utmost of them commanded good answers as numerous as 18 actors( 60), and an increase of 24 actors( 80) and a significance of 0.000, which means there is an increase in education regarding knowledge about the road to gentle birth. The instrument used is a questionnaire with validity and reliability with a calculated r of 0.946 > 0.60. Community service activities use methods and materials that are adjusted and packaged attractively so that all participants feel satisfied and enthusiastic about participating in a series of events till the very end. When the event is concluded, all participants practiced and conducted a question and answer session and mentoring for participants who did not understand well.